Presentation of a concrete additive manufacturing extruder with online rheology modification capabilities. Issue 1 (October 2021) - Poudelet, L; Castellví, A; Calvo, L; Cardona, R; Uceda, R; Fenollosa, F
Abstract: To date, Additive Manufacturing (AM), a driving technology for the Industry 4.0 paradigm, is a growing technology field but has not reached relevant impact in the construction sector. The reason exposed in this article is the fact that current capabilities in terms of control of the setting reaction of concrete in real time are limited. Experimentation with a state-of-the-art concrete AM print-head has evidenced that the full stabilization of concrete's chemical reactions is complex and involves phenomena that are not yet fully understood. Addressing this problem and the development of a fully automatic closed loop control would allow a great step forward in the capabilities of concrete additive manufacturing. So, as a first step, valuable information from thermal and pressure sensors were collected along the printing process, and their variations associated with the control of actuators (mixers and pumps) have been noted. A path for full real-time automatic control can be foreseen, and will guide future research and developments.